Analysis on clinical effects of dilation and curettage guided by ultrasonography versus hysteroscopy after uterine artery embolization in the treatment of cesarean scar pregnancy - Qiu J; Fu Y; Xu J; Huang X; Yao G; Lu W (Dove Medical Press, 2019)
Jian Qiu,1,2 Yunfeng Fu,1 Jiewei Xu,3 Xiaohong Huang,2 Guorong Yao,2 Weiguo Lu1 1Department of Gynecologic Oncology, Women’s Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang 310006, China; 2Department of Obstetrics and Gynaecology, Huzhou Central Hospital, Huzhou, Zhejiang 313000, China; 3Department of General Surgery, Huzhou Central Hospital, Huzhou, Zhejiang 313000, China Purpose: The purpose of this study was to investigate the efficiency, complications, and subsequent fertility outcomes of two methods in treating patients with cesarean scar pregnancy (CSP) after receiving uterine artery embolization (UAE) treatment.Patients and methods: A total of 62 CSP patients who visited our hospital and underwent UAE from January 2013 to January 2018 were retrospectively analyzed. Patients were either treated by dilation and curettage (D&C) guided by ultrasonography or hysteroscopy. The differences of related clinical indicators, clinical efficacy, complications, and subsequent fertility outcomes between the two groups were analyzed.Results: The rates of therapeutic success of the ultrasonography group and hysteroscopy group were 84.6% and 95.7%, respectively, the difference was not statistically significant (P=0.243). However, the intraoperative blood loss, duration of hospitalization, and overall complications were significantly lower in hysteroscopy group compared with D&C guided by ultrasonography group (P<0.05 for all). Meanwhile, hysteroscopy had the advantage of discovering potential diverticulum in the lower segment of anterior wall of uterus (P<0.001).Conclusion: D&C guided by ultrasonography or hysteroscopy for the treatment of CSP after UAE resulted in similarly good clinical outcomes. Compared with treatment of D&C guided by ultrasonography, hysteroscopy had less complications and had the advantages of discovering diverticulum. It can be used as an effective way for the treatment of CSP. Keywords: cesarean scar pregnancy, uterine artery embolization, dilation and curettage, ultrasonography-guided, hysteroscopy